The Effects of EPS, Company Size, and PER to Stock Price - Antonio, Alex (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to analyze the influence of Earnings Per Share (EPS), Price to Earnings Ratio (PER), and company size (SIZE) on stock prices in the Consumer Cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The research method used is multiple linear regression analysis, with a population of companies classified in the Consumer Cyclical sector. The results show that the independent variables EPS, PER, and company size have a significant positive effect on stock prices. This indicates that an increase in EPS, PER, and company size will be followed by an increase in stock prices in the Consumer Cyclical sector companies. Thus, these findings provide important implications for investors in considering these fundamental factors when making investment decisions in this sector.